2015
DOI: 10.1038/nrm.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond editing: repurposing CRISPR–Cas9 for precision genome regulation and interrogation

Abstract: The bacterial CRISPR–Cas9 system has emerged as a multifunctional platform for sequence-specific regulation of gene expression. This Review describes the development of technologies based on nuclease-deactivated Cas9, termed dCas9, for RNA-guided genomic transcription regulation, both by repression through CRISPR interference (CRISPRi) and by activation through CRISPR activation (CRISPRa). We highlight different uses in diverse organisms, including bacterial and eukaryotic cells, and summarize current applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
557
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 729 publications
(579 citation statements)
references
References 89 publications
1
557
1
7
Order By: Relevance
“…More studies on improving the fidelity and finding an alternative have been reported 1, 3, 4. To broaden the applicability of our delivery system, we explored other gene editing alternatives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More studies on improving the fidelity and finding an alternative have been reported 1, 3, 4. To broaden the applicability of our delivery system, we explored other gene editing alternatives.…”
Section: Resultsmentioning
confidence: 99%
“…Gene mutations and allele variations usually contribute to disease heterogeneity, which may result in treatment failure; thus, precision medicine‐based therapeutic approaches have increasingly attracted attention, especially since the CRISPR/Cas9 system was reported 1. The CRISPR/Cas9 system allows targeted genome editing, including frameshift knockout, gene insertion, and alteration, under the guidance of a specific guide RNA (gRNA) 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MxB knockout (KO) cell lines were generated by using the clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 gene system (Edit-R CRISPR-Cas9 gene engineering with SMARTCas9 nucleases; GE Healthcare) (32). The CRISPR genomic guide RNA sequences for human MxB in THP-1 and HT-1080 cells were designed to target exon 2 near the start codon.…”
Section: Generation Of Mxb Knockout Human Cellsmentioning
confidence: 99%
“…Second, the "overlapping gene problem"-technologies like Cre-lox or CRISPR, which supposedly cleanly alter gene expression, often do not 73 . Roughly 10% of genes in the mouse genome have overlapping reading frames 74 .…”
Section: Reviewmentioning
confidence: 99%